PENGELOMPOKAN KASUS PENYAKIT AIDS BERDASARKAN PROVINSI DENGAN DATA MINING K-MEDOIDS CLUSTERING - Leonardo Purba; Saifullah Saifullah; Rafiqa Dewi (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2019)
Acquired Immunodeficiency Syndrome or Acquired Immune Deficiency Syndrome (AIDS abbreviated) is a set of symptoms and infections that arise due to the destruction of the human immune system due to HIV viral infection. This study discusses about Rapidminer Application in Grouping Cases of AIDS Disease by Province with K-medoid Clustering Data Mining. The rise of AIDS cases in Indonesia has become a case that never escapes government attention. Attention to the ever increasing rate of death makes people worry about the spread of the AIDS virus. Sources of data and research are collected from the information document Number of Villages Who Have Health Facilities produced by the Social Security Administering Board. The data used in this study is data from 2008-2011 which consists of 34 provinces. Assessment criteria used are 2 ie 1). the average number of AIDS cases and 2). the average number of AIDS cases deaths were managed using 3 clusters ie high cluster level (C1), medium cluster level (C2) and low cluster level (C3). So that the cluster C1 obtained for Cases of AIDS Disease by Province as many as 4 provinces of Papua, DKI Jakarta, West Java and East Java, 9 provinces for cluster C2 and for cluster C3 as much as 20. This can be input to the government, the province of concern in the number of cases of AIDS.Keywords: Maining Data, AIDS Disease, Clustering, K-medoid